Youth transitions out of state care : being recognized as worthy of care, respect, and support - Glynn, Natalie (Emerald Publishing Limited, 2023)
The point of leaving care has been identified as a potentially critical turning point at which services might moderate later outcomes. While there is growing evidence identifying social support and identity development as crucial elements, there remains a gap in the understanding of the care-leaving process from the perspective of young people. Youth Transitions Out of State Care: Being Recognized as Worthy of Care, Respect, and Support presents a newly developed theoretical framework for understanding this process. Supported by research from a qualitative longitudinal study of leaving state care at the age of 18, Dr. Natalie Glynn presents an intimate account of the personal circumstances and structural elements influencing the transitions of rural and urban young people in Ireland using three illustrative cases that break new ground by centering on the voices of young people and their distinct yet interconnected experiences. Pulling together agentic and structural elements in the transition to explain how young people's choices and reactions are influenced by their personal journeys and socio-cultural contexts, Glynn creates a new theoretical framework that social workers and researchers can use to comprehend this transition period when working with care leavers. Utilizing Ireland as a case study of the increasingly prevalent model of aftercare provision, Youth Transitions Out of State Care: Being Recognized as Worthy of Care, Respect, and Support details broad policy implications and presents an opportunity to understand how this approach to supporting care leavers works in practice.
Keywords: Youth -- Services for -- Ireland -- Case studies.; Social work with youth -- Ireland -- Case studies.; Youth -- Institutional care -- Ireland -- Case studies.; Political Science -- Public Policy / Social Services & Welfare.; Social welfare & social services.; elektronické knihy; electronic books